Designed trimer-mimetic TNF superfamily ligands on self-assembling nanocages. (October 2018) - Kih, Minwoo; Lee, Eun Jung; Lee, Na Kyeong; Kim, Yoon Kyoung; Lee, Kyung Eun; Jeong, Cherlhyun; Yang, Yoosoo; Kim, Dong-Hwee; Kim, In-San
Abstract: Presentation of an endogenous bioactive ligand in its native form is a key factor in controlling and determining its bioactivity, stability, and therapeutic efficacy. In this study, we developed a novel strategy for presenting trimeric ligands on nanocages by designing, optimizing and testing based on the rational design, high-resolution structural analysis and agonistic activity assays in vitro and in vivo . We successfully designed a nanocage that presents the TNF superfamily member, TRAIL (TNF-related apoptosis-inducing ligand) in its native-like trimeric structure. The native structure of TRAIL complexes was mimicked on the resulting trimeric TRAIL-presenting nanocages (TTPNs) by inserting sufficient spacing, determined from three-dimensional structural models, to provide optimal access to the corresponding receptors. The efficacy of TTPNs as an anti-tumor agent was confirmed in preclinical studies, which revealed up to 330-fold increased affinity, 62.5-fold enhanced apoptotic activity, and improved pharmacokinetic characteristics and stability compared with the monomeric form of TRAIL (mTRAIL). In this latter context, TTPNs exhibited greater than 90% stability over 1 mo, whereas ∼50% of mTRAIL aggregated within 2 d. Consistent with their enhanced stability and ultra-high affinity for the TRAIL receptor, TTPNs effectively induced apoptosis of tumor cells in vivo, leading to effective inhibition of tumor growth. Although TRAIL was used here as a proof-of-concept, all members of the TNF superfamily share the TNF homology domain (THD) and have similar distances between ecto-domain C-termini. Thus, other TNF superfamily ligands could be genetically substituted for the TRAIL ligand on the surface of this biomimetic delivery platform. Graphical abstract: Image 1